2010
DOI: 10.1007/s00134-010-1796-6
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability of manual muscle strength testing in ICU survivors and simulated patients

Abstract: Objective-The goal of the paper is to determine inter-rater reliability of trained examiners performing standardized strength assessments using manual muscle testing (MMT).Design, subjects, and setting-The authors report on 19 trainees undergoing quality assurance within a multi-site prospective cohort study.Intervention-Inter-rater reliability for specially trained evaluators ("trainees") and a reference rater, performing MMT using both simulated and actual patients recovering from critical illness was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 21 publications
1
92
2
8
Order By: Relevance
“…Of these patients, 20% died before hospital discharge, 7% died after discharge and before initial follow-up, and 25% met exclusion criteria ( Figure 1). For the 203 survivors who consented and were eligible for follow-up in this study (29 At 6-month follow-up, the mean (6 SD) muscle strength, as a percentage of maximum MRC sum-score, was 92% (6 8%), with 8% (13 of 169) having ICUacquired weakness, and the mean (6 SD) percent-predicted values for 6MWT and SF-36 PF were 64% (6 22%) and 61% (6 36%), respectively. There was relatively small improvement observed in mean physical outcome measures between 6 and 12 months (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of these patients, 20% died before hospital discharge, 7% died after discharge and before initial follow-up, and 25% met exclusion criteria ( Figure 1). For the 203 survivors who consented and were eligible for follow-up in this study (29 At 6-month follow-up, the mean (6 SD) muscle strength, as a percentage of maximum MRC sum-score, was 92% (6 8%), with 8% (13 of 169) having ICUacquired weakness, and the mean (6 SD) percent-predicted values for 6MWT and SF-36 PF were 64% (6 22%) and 61% (6 36%), respectively. There was relatively small improvement observed in mean physical outcome measures between 6 and 12 months (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…ICUAW was defined as MRC sum score for muscle strength to be Ͻ48, provided no other cause of weakness could be identified (147). Since then, many other publications have used the MRC sum score to diagnose ICUAW (10,44,51,143,144,149,189,273,305,325,413,499,536,598,623,632) without referring to the precise underlying disease entity (FIGURE 1B). This clinical approach revealed that weakness affects proximal muscles more than distal muscles (147,305,413).…”
Section: B Aspects Of Clinical Evaluation and Diagnosticsmentioning
confidence: 99%
“…The MRC sum score was proposed as a routine and first line screening tool in the ICU for patients at risk for developing ICUAW (268,402,622,661). As reported in various clinical settings [mechanically ventilated patients with acute stroke (267), Guillain-Barré syndrome (369), stimulants (189), post ICU (40, 325)], inter-rater reproducibility was found to be good in a large study of critically ill patients (301), and one smaller series (10), but not in two other small studies (129,325). Methodological issues such as judging the adequate awakening and cooperation of the patient required to perform the test may be very important.…”
Section: B Aspects Of Clinical Evaluation and Diagnosticsmentioning
confidence: 99%
“…Th ese include the 4-m timed walk speed (in meters per second), [24][25][26] manual muscle testing using the Medical Research Council sum score 27,28 (range, 0-60, with , 48 indicating ICU-acquired weakness 29 ), and spirometry 30 (reported as FEV 1 % predicted based on normative values 31 ). Patient-reported measures included the Medical Outcomes Survey 36-Item Short Form (SF-36) 32 PF domain, the Functional Performance Inventory 33 overall score, and the Euro-QOL (EQ-5D) 34 mobility subscale.…”
Section: Study Measuresmentioning
confidence: 99%